Electroacupuncture and Parecoxib Reduce Inflammatory Injury in a Primary Dysmenorrhea Rat Model: Investigating the Role of the COX-2/NF-κB/NLRP3 Pathway - Xue X; Wang S; Li J; Yuan H; Pan S; Liu X; Yue Z; Liu Y (Journal of Pain Research, 2025)
Xiao Xue,1,2 Shaohua Wang,2 Juan Li,2 Hanyu Yuan,2 Sian Pan,2 Xin Liu,1 Zenghui Yue,2 Yu Liu2 1The First Affiliated Hospital, Department of Chinese Medicine, Hengyang Medical School, University of South China, Heng yang, Hunan, 421000, People’s Republic of China; 2College of Acupuncture, Massage and Rehabilitation, Hunan University of Chinese Medicine, Changsha, 410208, People’s Republic of ChinaCorrespondence: Zenghui Yue; College of Acupuncture, Massage and Rehabilitation, Hunan University of Chinese Medicine, Changsha, 410208, People’s Republic of China, Tel +86 13787293866, Fax +86 - 0731 – 88458189, Email yue5381316@126.com Yu Liu, College of Acupuncture, Massage and Rehabilitation, Hunan University of Chinese Medicine, Changsha, 410208, People’s Republic of China, +86 – 15084947646, Fax +86 - 0731 – 88458189, Email luveyu@126.comPurpose: Anti-inflammatory drugs relieve primary dysmenorrhea (PDM), and nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) is a potential treatment target. Electroacupuncture (EA) is an effective alternative strategy for treating PDM as it regulates the NLRP3 inflammasome. However, the exact anti-inflammatory mechanism of EA remains unclear. Therefore, this study explored the therapeutic effect of EA on PDM and determined the potential involvement of the cyclooxygenase-2 (COX-2)/nuclear factor κB (NF-κB)/NLRP3 signaling pathway.Patients and Methods: The following pain management interventions were administered to a PDM rat model: saline (control), EA, parecoxib, EA + parecoxib, or ibuprofen. After treatment, the following parameters were examined: torsion behavior; endometrial histopathological morphology and ultrastructure; serum and uterine prostaglandin E2 (PGE2) and prostaglandin F2α (PGF2α) levels; nuclear translocation of NF-κBp65; and the expression of COX-2, phospho-NF-κBp65. NF-κBp65, NLRP3, apoptosis-associated spec-like protein (ASC), pro-cysteine aspartate-specific protease 1 (pro-caspase-1), cysteine aspartate-specific protease 1 (caspase-1), interleukin (IL)-1β, and IL-18.Results: The treatment groups showed considerably reduced pathological uterine injury compared with that of the control. This was associated with decreased PGF2α and increased PGE2 levels. The uterine tissues in the treatment groups showed reduced NF-κBp65 nuclear translocation and a decreasing trend in COX-2, NF-κBp65, phospho-NF-κBp65, NLRP3, ASC, pro-caspase-1, caspase-1, IL-1β, and IL-18 protein expression compared with that of the controls. The levels of each protein in the parecoxib and ibuprofen groups did not differ considerably from those in the EA group. Furthermore, EA markedly improved pain symptoms and pathological damage in PDM rats and downregulated the expression of COX-2/NF-κB/NLRP3 signaling pathway proteins in uterine tissue.Conclusion: Our findings demonstrated superior anti-inflammatory effects of EA + parecoxib on COX-2/NF-κB/NLRP3 signaling pathway-related proteins compared with that of EA alone or single-drug administration.Keywords: anti-inflammatory treatment, cyclooxygenase-2, prostaglandin, nuclear transcription factor, nucleotide-binding oligomerization domain-like receptor 3